Expressions of matrix metalloproteinases-1 and-9 and opioid growth factor in rabbit cornea after lamellar keratectomy and treatment with 1% nalbuphine - Silva, Miguel Ladino; Ribeiro, Alexandre Pinto; Silva, Germana Alegro; Barbosa Sanchez, Irma Ximena; Renzo, Roberta; Uscategui, Ricardo; Lima, Tiago Barbalho; Aldrovani, Marcela; Laus, Jose Luiz (Consel Brasil Oftalmologia, 2015)
Purposes: To evaluate the effects of nalbuphine 1% on the expression of metalloproteinase 1 (MMP-1), metalloproteinase 9 (MMP-9), and opioid growth factor (OGF) in rabbit corneas after lamellar keratectomy. Methods: The rabbits were assigned to two groups: group nalbuphine (GN, n=30), which received 30 mu L of nalbuphine 1% in 4 daily applications at regular intervals until corneal epithelialization, and group control (GC, n=30), which received physiological saline solution under the same conditions adopted in GN. The corneas were collected for immunohistochemistry on days 1, 3, 5, 7, and 9 after lamellar keratectomy, and the expressions of MMP-1, MMP-9, and OGF were analyzed. Results: The expressions of MMP-1 and MMP-9 increased until day 5 of the evaluation, with no differences observed between GN and GC (p>0.05). On days 7 and 9, significant reductions were observed in the expression of MMP-1 (p<0.01), with no differences observed between GN and GC (p>0.05). The expression of OGF was constant in all periods (p>0.05), restricted to the corneal epithelium, and there was no difference between the groups (p>0.05). Conclusions: The study results showed that nalbuphine 1% did not alter the expression patterns of MMP-1, MMP-9, and OGF in rabbit corneas after lamellar keratectomy.
Keywords: Cornea; Photorefractive keratectomy; Nalbuphine/therapeutic use; Matrix metalloproteinases; Receptors; opioid; Immunohistochemistry; Animals; Rabbits